To make sports educational (Journal of Parents and Teachers, 2024)
Sometimes, it is challenging to see the educational aspect of Physical Education. In this article, a Physical Education teacher discusses its importance and its connection with personality. Analyzing certain sports situations, she concludes that these reflect the true nature of her students. Through these reflections, she aims to guide and educate them for their daily lives. Values such as teamwork are crucial in sports, and aspects like coping with failure can be effectively taught through the subject. Finally, she also briefly discusses who can or cannot be educators in sports.